Complex metacommunity structure for benthic invertebrates in a low‐diversity coastal system. Issue 22 (22nd October 2015) - Valanko, Sebastian; Heino, Jani; Westerbom, Mats; Viitasalo, Markku; Norkko, Alf
Abstract: The majority of studies in metacommunity ecology have focused on systems other than marine benthic ecosystems, thereby providing an impetus to broaden the focus of metacommunity research to comprise marine systems. These systems are more open than many other systems and may thus exhibit relatively less discrete patterns in community structure across space. Metacommunity structure of soft‐sediment benthic invertebrates was examined using a fine‐grained (285 sites) data set collected during one summer across a large spatial extent (1700 km 2 ). We applied the elements of metacommunity structure (EMS) approach, allowing multiple hypothesis of variation in community structure to be tested. We demonstrated several patterns associated with environmental variation and associated processes that could simultaneously assemble species to occur at the sites. A quasi‐Clementsian pattern was observed frequently, suggesting interdependent ecological relationships among species or similar response to an underlying environmental gradient across sites. A quasi‐nested clumped species loss pattern was also observed, which suggests nested habitat specialization. Species richness declined with depth (from 0.5 to 44.8 m). We argue that sensitive species may survive in shallower water, which are more stable with regard to oxygen conditions and present greater habitat complexity, in contrast to deeper waters, which may experience periodic disturbance due to hypoxia. Future studies should better integrate disturbance in terms of temporal dynamics and dispersal rates in the EMS approach. We highlight that shallow water sites may act as sources of recruitment to deeper water sites that are relatively more prone to periodic disturbances due to hypoxia. However, these shallow sites are not currently monitored and should be better prioritized in future conservation strategies in marine systems. Abstract : The majority of studies in metacommunity ecology have focused on systems other than marine benthic ecosystems. We applied the elements of metacommunity structure (EMS) approach on a soft‐sediment benthic invertebrates data set (285 sites, 1700 km 2 ) to explore several patterns associated with environmental variation and associated processes that could simultaneously assemble species to occur at the sites. Complex metacommunity structure for benthic invertebrates in a low‐diversity coastal system may thus be a typical feature of highly connected systems, highlighting the need to better incorporate disturbance in terms of temporal dynamics and dispersal rates in the EMS approach.